Diversity of Managerial Ideology (The Chinese Management Book-of-Readings Series,, 2018)
This book is the first in a series on Chinese management based on the Global Chinese Management Conferences (from 2015 to 2017), an annual conference organized by the Sun Tzu Art of War Institute. The first volume is by FOO Check Teck, professor at Fudan and Hunan University and founding editor of Chinese Management Studies (SSCI), who encourages readers to broaden their minds to embrace the Universe as a Community. The book argues that the lives of all beings are worth preserving and urges the academic community to recognize the ideologies at heart of management and to see research as a deep, reflective thinking process that goes far beyond the testing of hypotheses - great works, lasting 2,500 years are the result of deep reflection upon experiences. It also calls for the re-framing of management integration of a variety of ideological strands, typically in topics in MBA or MPA programs: earnings, mobility of human capital, complex adaptive systems, HRM (in small high-tech firms), technology standardization, Xin (trust: labor relations), multi-leveling, re-forming (hospitals), He-Xie (doctoral work), upgrading (automobile industry). The major consequential consideration must be what it means for people. .